Prevalence and intensity of helminth parasites in the snake headed fish, Channa punctatus of Savar, Dhaka (Jahangirnagar University Journal of Biological Sciences, 2016)
Ten species of helminth parasites i.e. Neopecoelina saharanpuriensis, Mesolecitha linearis, Asymphylodora tincae, Genarchopsis bangladensis, Ditestolepis diphana, Senga sp., Neoechinorhynchus tylosuri, Pallisentis sp., Ascardia larvae., Gnathostoma spinigerum were identified from Channa punctatus of Savar area. Majority of the parasites were found in the intestine. The overall prevalence of infection of the parasites was 32.5% and the mean intensity was 1.46±1.29. Both the prevalence (34.61%) and mean intensity (1.5±1.21) were higher in male fishes than the female fishes (28.57% and 1.375± 0.99 respectively). The prevalence (13.75%) and mean intensity (1.64± 0.67) of trematodes were the highest among the parasites groups. Both the prevalence and mean intensity were the highest in the intermediate length (10.1-15.1cm) and weight (21-31gm) groups of fishes.Jahangirnagar University J. Biol. Sci. 4(1): 1-7, 2015 (June)